What is netnography? - Kozinets, Robert V., 1964- ([Thousand Oaks, Calif. : SAGE], 2011)
The speaker defines netnography as an adaptation of ethnography for the online world, for the requirements of online communities and online cultures.
Online video.
Includes transcript.
Specialized.
Description based on online resource; title from home page (viewed on Feb. 4, 2012).
Keywords: elektronické knihy; electronic books; Ethnology -- Computer network resources; Ethnology -- Research